(untitled) (REMUNOM, 2025)
This article seeks to understand how the transition from Early Childhood Education to Elementary School happens, with an emphasis on the perspective of the children who experience this moment. The research was conducted in a public school in Linhares, Espírito Santo, involving students in the first year of Elementary School. Interviews were conducted to address topics such as the physical structure of the school, the feeling of belonging, the emotions experienced, and the relationship with the subject. During this study period, it was noticeable that, although many children showed joy and happiness with this new stage, we also noticed insecurities, fears, and longing for their old routine/school. We also observed that the distancing from playful practices and the demand for results can end up making it difficult for students to adapt. Therefore, we emphasize the importance of a sensitive welcome on the part of teachers, as well as the maintenance of some Early Childhood Education practices in the first years of Elementary School. Based on listening to the children, the work will point out ways for this transition to be carried out more smoothly, respecting each child’s time and favoring a positive school experience. Therefore, more than just fulfilling a curriculum, it is of utmost importance that the school is committed to the well-being and development of students from the first steps in the new stage of schooling.